Conductivity Studies of Epoxidized PMMA Grafted Natural Rubber Doped Lithium Triflate Gel Polymer Electrolytes - Nazir, Khuzaimah; Fariz Mohamad Taib, Mohamad; Zakaria, Rosnah; Kamil Yaakob, Muhamad; Hasdinor Hassan, Oskar; Zu Azhan Yahya, Muhd; Malik Marwan Ali, Ab (International Journal of Engineering and Technology, 2019)
A gel polymer electrolytes (GPEs) comprising of 62.3 mol% of epoxidized-30% poly(methyl methacrylate) grafted natural rubber (EMG30) as a polymer host, LiCF3SO3 as a dopant salt and ethylene carbonate (EC) as a plasticizer was prepared by solution-casting technique. The effect of plasticizer on the EMG30- LiCF3SO3 on the ionic conductivity is explained in terms of the plasticizer loading of the film. The temperature dependence of the conductivity of the polymer films obeys the Vogel-Tamman-Fulcher (VTF) relationship. The ionic transference number is calculated using Wagnerâ€™s polarization technique shows that the conducting species are predominantly due ions and hence showed the system is an ionic conductor. Surface morphological analysis showed the sample with the highest conductivity exhibited most homogenous in nature.Â Â